MEMIKIRKAN KEMBALI PERSPEKTIF SOSIOLOGIS: Upaya Peningkatan Mutu Kualitas Artikel di Jurnal Sosiologi Reflektif - Yayan Suryana; Achmad Zainal Arifin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
This article aims to enhance the quality of paper submitted to Jurnal Sosiologi Reflektif (JSR) by exploring some weaknesses of submitted articles to JSR within two last editions of using online journal system. Based on reasons used by the management of JSR in rejecting submitted articles at the first stage, which shows that around 23 percent of them are due to the lack of sociological perspective or framework, it is important to reconsidering the meaning of employing sociological perspective the the article. The ability to understand the basic characteristics of sociological analysis becomes the most fundamental requirements in producing a good sociological article. How we should formulate a good sociological question will determine the quality of a sociological paper. At this point, reconsidering and understanding how we should use a basic concept of sociological imagination in formulating a research question will help to focus an article on being strongly considered as sociological, in addition to the use of sociological theories. Besides, many articles are not built upon an adequate literature review. Some of them use literature reviews as making a summary of other people have done without further discussing their differences and contributions both theoretically and practically.